The Influence of Knowledge, Service Quality, Trust, and Perceived Value on Sharia Fintech Customer Satisfaction - Siti Ismi Diningty Fauzi; Irfan Syauqi Beik; Jono Mintarto Munandar (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2022)
The existing fintech in Indonesia is changing the landscape of the global financial sector significantly. Using SEM-PLS analysis, this study aims to determine the effect of knowledge, service quality, trust, and perceived value on customers’ satisfaction of sharia fintech. Using the sharia fintech ALAMI customers, this study finds that knowledge, trust, quality of services, and perceived behavior have a positive significant influence on ALAMI's customer satisfaction. This could be attributed to the easy access provided by fintech.